Peningkatan Kompetensi Pedagogik Guru Sains SMP-SMA Negeri 1 Sesayap Kabupaten Tana Tidung Melalui Science Technology Literacy (STL) dan Pengembangan Potensi Lokal - Endik Deni Nugroho; Fadhlan Muchlas Abrori (Jurnal Pengabdian Pada Masyarakat, 2017)
Science teacher's role in improving the quality of learning is an urgent problem that must be realized. To encourage ongoing activities, the teacher needs to review / discuss activities, identify the obstacles programs that have been implemented, as well as practicing teachers' activities focused on developing lesson plans. Efforts that can be done is through mentoring and building-based learning Science Technology Literacy (STL) and the local potential. Some of the activities that have been carried out, namely socialization program, Counseling, Training, Mentoring, Teaching Dissemination of Results and Build Networking Skills. Based on the results of the activities as much as 60% of the 10 science teachers in SMP-SMA Negeri 1 Sesayap not understand the STL and the development of local potential. After the training and mentoring as many as 10 teachers have been able to make the device and implement STL learning and developing local potential in the classroom.